High concentrations of atorvastatin reduce in-vitro function of conventional T and regulatory T cells (2019)
ABSTRACT: Regulatory T cells (Tregs ) modulate the magnitude of immune responses and possess therapeutic potential in an array of immune diseases. Statins reduce the activation and proliferation of conventional T cells (Tcons ), and they seem to up-regulate the frequency and function of Tregs . However, there is a lack of simultaneous evaluation of the in-vitro effect of statins on the functional profile of Tregs versus Tcons . Herein, magnetically purified Tcons and Tregs were stimulated with CD3/CD28/interleukin (IL)-2 in the presence of atorvastatin (ATV) at 1 or 10 µM. The suppressive function of Tregs , the expression of markers associated with Treg function, activation levels, cytokine production and calcium flux in both subpopulations were assessed by flow cytometry. ATV had no cytotoxic effect on T cells at the concentrations used. Interestingly, 10 µM ATV hampered the suppressive capacity of Tregs . Moreover, this higher concentration reduced the expression of forkhead box protein 3 (FoxP3), cytotoxic T lymphocyte antigen (CTLA-4) and programmed death 1 (PD-1). In Tcons , ATV at 10 µM decreased PD-1 and CD45RO expression. The expression of CD25, CD69, CD95, CD38, CD62L, CCR7 and perforin was not affected in both subpopulations or at any ATV concentrations. Remarkably, 10 µM ATV increased the percentage of tumour necrosis factor (TNF)-α-producing Tregs . Although there was a reduction of calcium flux in Tcons and Tregs , it was only significant in 10 µM ATV-treated Tcons . These results suggested that 10 µM ATV affects the cellular functions of both populations; however, this concentration particularly affected several aspects of Treg biology: its suppressive function, cytokine production and expression of Treg -specific markers.